RECK in Osteosarcoma: A Novel Role in Tumour Vasculature and Inhibition of Tumorigenesis in an Orthotopic Mode - Clark, J.; Akiyama, T.; Thomas, D.; Labrindis, A.; Evdokiou, A.; Galloway, S.; Kim, H.; Dass, Crispin; Choong, P. (John Wiley & Sons, Inc., 2011)
Targeted therapy in osteosarcoma (OS) is needed to improve patient outcomes. Human RECK may have a role because it inhibits cancer invasion and regulates angiogenesis. This study aimed to characterize RECK expression in human OS, to examine in vitro effects of RECK on vascular endothelium and OS cell behavior, and to analyze the effect of RECK on OS grown orthotopically in nude mice. METHODS: RECK was examined in human OS samples. Interactions between RECK and VEGF were studied in tissue and cells. RECK transfection was used to study its effects on vascular endothelial (HMEC-1) and OS (SaOS-2) cell behavior in vitro and in vivo. SaOS-2 co-culture with RAW 246.7-derived osteoclasts on osteoslides was used to assess effects on osteoclast activity. RESULTS: RECK was absent from OS cells but was expressed in tumor vessel endothelium. Via microarray analysis, RECK mRNA was elevated in samples with low proliferative activity, a trend most evident in poorly differentiated samples. VEGF induced RECK expression in HMEC-1. RECK transfection inhibited HMEC-1 invasion and induced thicker, although more numerous, tube formation. RECK inhibited SaOS-2 invasion, proliferation, colony formation, and osteoclast activity but supported SaOS-2 adhesion to collagen I. In vivo, RECK inhibited SaOS-2 tumor growth, bone destruction, and consequent metastasis. CONCLUSIONS: RECK expression is downregulated in highly proliferative OS but is present in tumor vessels and upregulated in endothelium by VEGF. RECK inhibits invasion and tumorigenic properties in SaOS-2, as confirmed in vivo. Further testing of RECK delivery in OS is warranted.